(untitled) (Bangladesh Journal of Medical Biochemistry, 2014)
The protective effects of ethanolic extract of Tamarindus indica leaves and seeds in compoarison to vitamin E, were studied on paracetamol induced hepatotoxicity in Long Evans Rats. Different groups of animals were administered in the paracetamol (1500mg /kg, p.o.) for 7 days. Ethanolic extracts of leaves and seeds of Tamarindus indica (1250mg/kg) with parallel vitamin E (500 mg/kg), were administered to paracetamol pretreated rats. On treatment with paracetamol a significant increase in alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin and alkaline phosphatase were observed. On administration of ethanolic extracts of leaves and seeds a significant decrease in the level of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin and alkaline phosphatase (ALP) were observed and histopathological examination of liver tissue revealed an almost return to normal architecture. The result were almost comparable to vitamin E, a known hepatoprotective agent. DOI: http://dx.doi.org/10.3329/bjmb.v6i2.17645 Bangladesh J Med Biochem 2013; 6(2): 63-67